Kultura a problem zacofania - Banach , Wiesław (Człowiek i Społeczeństwo, 2014)
The aim of this paper is to present and examine the link between culture and economic backwardness. One of the main questions of economic thought is: why some are so rich and some so poor? Traditional explanations like imperialism, dependency and racism are no longer adequate, and increasingly observers are concluding that the principal reason why some countries and ethnic groups are better off than others lies in cultural values, which powerfully shape political, economic and social performance. According to many authors (Lawrence E. Harrison, Samuel P. Huntington, Peter Berger, David Landes, Mariano Grondona, Francis Fukuyama, Robert Putnam, Ronald Inglehart, Michael Porter) adequate values, axiological determinants and other cultural factors (like customs, beliefs attitudes, trust in the individual, the moral imperative, the value of work) have a very positive impact on the economic development of each society. The paper is an attempt to show why the category of backwardness is more appropriate and helpful for the understanding of the role of culture than the category of development.